Morphological analysis of Asheninka toponyms with the ending "ni" - Romaní, Maggie (2003)
This work is a study on asheninka toponomies. Here we will analyse a group of utterances from the morphological viewpoint. The utterances work as geographical nouns from the Gran Pajonal area (Central Peruvian Jungle). These toponimies are the ones which end in the suffix -ni, which have drawn our investigating interest. Though research in toponomies has increased and improved, we know there are no studies about the toponomies from this area. In the light of this we are certain that this study will prove of great contribution to the global knowleage of Amazon toponomies. Besides, it will be quile useful to those who are engaged in the investigation of this phenomenon in the Asheninka language.